TRANSLATION AS ONE OF THE METHODS OF LEARNING FOREIGN LANGUAGES BY SPECIALTY (Archive of Conferences, 2020)
At present, when the language has become a means of obtaining world scientific and technical information, there is an increasing need for students to develop certain translation skills, which should help to realize their needs to practically use the language being studied. Among the tasks of translation, two can be distinguished